2019
DOI: 10.1155/2019/5874603
|View full text |Cite
|
Sign up to set email alerts
|

Association between Duration of Exercise (MET Hours per Week) and the Risk of Decreased eGFR: A Cross-Sectional Study Based on a Large Chinese Population

Abstract: Background. Physical activity is effective in preventing chronic diseases. However, the impact of different durations of exercise on human health is unknown, especially among people with diabetes or prediabetes. Objective. To explore the relationship between high MET hours per week and the change in glomerular filtration rate (eGFR) in the total population and different subgroups. Methods. A total of 43767 individuals from eight provinces, in China, were recruited. Logistic analysis was used to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…Our finding showed that the high activity group (≥3000 METs-min/week) was positively associated with the risk of incident CKD. A similar result was reported in a cross-sectional study by Wang et al [ 40 ] indicating that the high-intensity exercise group was associated with decreased eGFR (≤90 mL/min/1.73 m 2 ). These results imply the importance of the proper intensity and time of exercise for high-risk subjects with incident CKD, and the possible differential association between physical activity and CKD needs to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding showed that the high activity group (≥3000 METs-min/week) was positively associated with the risk of incident CKD. A similar result was reported in a cross-sectional study by Wang et al [ 40 ] indicating that the high-intensity exercise group was associated with decreased eGFR (≤90 mL/min/1.73 m 2 ). These results imply the importance of the proper intensity and time of exercise for high-risk subjects with incident CKD, and the possible differential association between physical activity and CKD needs to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 88%
“…The eGFR's result had a higher value (lower risk) than control group. It was consistent with eGFR's result by using duration of exercise training in large Chinese population 4,9 and aerobic exercise training in non-dialysis chronic kidney disease 5 . It helps improving the vascular function and maintain the function of the arteries.…”
Section: Discussionsupporting
confidence: 84%
“…A meta-analysis found that physical activity can help improve the eGFR (by 5.22 mL/min/1.73 m 2 ) with short-term exercise (<3 months), but not with 3–6 months of exercise or 6–12 months of exercise in CKD patients, indicating the diverse effects of different modes and amounts of exercise on eGFR [ 50 ]. In contrast, a cross-sectional study based on the Chinese population reported that >7.5 MET-hours per week was significantly associated with the risk of decreased eGFR in participants without a history of kidney diseases, aged from 55–65 years, but not in participants younger than 55 or older than 65 years [ 51 ]. It is hypothesized that in certain age groups of the Chinese population, light-to-moderate physical exercise increases the risk of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%